CAN ULTRASOUND ABDOMEN HELP IN EARLY DIAGNOSIS OF DIABETES MELLITUS? AN OBSERVATIONAL STUDY - Anwar, Javed; Aamir, Muhammad Omer; Sanaullah, Sanaullah; Imdad, Zeeshan ul Hasnain; Parveen, Ishrat; Yousaf, Nasreen (Journal of Ayub Medical College Abbottabad, 2015)
Background: Diabetes mellitus is a common disease. Similarly, ultrasound findings of fatty change and renal crystals are commonly seen on ultrasound. In the personal observation of the main author over the past so many years it was noticed that Diabetes Mellitus, Fatty liver and renal crystals all sit well together. This study tries to establish a relationship between diabetes mellitus renal echogenic foci and fatty liver. This study is first of its kind, as nobody has ever before investigated an association between the renal echogenic foci and fatty liver in relation to diabetes mellitus. Methods: This cross-sectional, observational study was conducted at Radiology Department Combined Military Hospital, Kohat From 2nd June 2013 to 30th May 2014. Three hundred patients were collected on the basis of having fatty liver and renal echogenic foci on ultrasound and three hundred more patients were collected who had no fatty liver or renal echogenic foci on ultrasound. Their labs were done for diabetes mellitus. Results: The patients having renal echogenic foci together with fatty liver had 83% positive rate of being diabetics, while patients with no fatty liver and no echogenic foci on ultrasonography had only 0.6% Positive rate of being diabetics. Conclusion: Our results provided the first demonstration of an association between renal echogenic foci together with fatty liver with the diabetes mellitus. Thus ultrasound examination of abdomen can be helpful in its early diagnosis if we make a protocol of doing fasting and random blood sugars in all those patients who have positive renal echogenic foci and fatty liver on their ultrasound examination.